Valuation of Executive Stock Options and the FASB Proposal: An Extension. - Foster III, Taylor W.; Koogler, Paul R. (The Accounting Review, 1993)
Comments on the valuation of executive stock options (ESO) and the fair value proposal of the Financial Accounting and Standards Board. Stability of the added parameter; Compatibility of lambda and the numerical method with accounting policy; Analysis of the ESO estimation.